2
$\begingroup$

I have $f_{\tau, \theta}(y)=\theta e^{-\theta(y-\tau)}, y\ge\tau, \theta\gt 0$. Assume both parameters unknown.

$\mu_1=E(Y)=\tau+\frac1\theta=\bar{Y}=m_1$ where $m$ is the sample moment.

$\mu_2=E(Y^2)=(E(Y))^2+Var(Y)=(\tau+\frac1\theta)^2+\frac{1}{\theta^2}=\frac1n \sum Y_i^2=m_2$.

$\mu_2-\mu_1^2=Var(Y)=\frac{1}{\theta^2}=(\frac1n \sum Y_i^2)-{\bar{Y}}^2=\frac1n\sum(Y_i-\bar{Y})^2\implies \hat{\theta}=\sqrt{\frac{n}{\sum(Y_i-\bar{Y})^2}}$

Then substitute this result into $\mu_1$, we have $\hat\tau=\bar Y-\sqrt{\frac{\sum(Y_i-\bar{Y})^2}{n}}$

Is my procedure correct?

$\endgroup$
3
$\begingroup$

There is a small problem in your notation, as $\mu_1 =\overline Y$ does not hold. The term on the right-hand side is simply the estimator for $\mu_1$ (and similarily later). But your estimators are correct for $\tau, \theta$ are correct.

$\endgroup$
  • $\begingroup$ Maybe better wording would be "equating $\mu_1=m_1$ and $\mu_2=m_2$, we get ..."? $\endgroup$ – CoolKid Oct 1 '17 at 22:08
  • $\begingroup$ A better wording would be to first write $\theta = (m_2 - m_1^2)^{-1/2}$ and then write "plugging in the estimators for $m_1, m_2$ we get $\hat \theta = \ldots$". $\endgroup$ – Dominik Oct 1 '17 at 22:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.